Challenges in Work and Employment during the COVID-19 Pandemic - Kalliola, Satu; Heiskanen, Tuula (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue reprint consists of 10 research articles published in "Challenges in Work and Employment during the COVID-19 Pandemic. The authors, originating from six countries, have studied different professional and occupational groups during the pandemic. Their topics range from theoretical analysis of remote work to the experiences of self-leadership, and from new types of job demands to new support needs required to experience relatedness in the pandemic era.